Human and Social Dimensions of Climate Change - Chhetri, Netra (IntechOpen, 2012)
Anomalous climatic outcomes such as higher temperatures, intense rainfall and flood, frequent and severe droughts are now at the new level. Without appropriate adaptation measures, climate change is bound to exacerbate vulnerability of society, place food security and human health at risk, threaten the lives of growing urban population and impede the goal of attaining sustainable development. The human and social dimensions of climate change, including climate policy, are essential parts of our response to the many challenges emanating from climate change. By focusing on a wide range of topics and involving a diverse array of scholars, this book sheds lights on human and social dimensions of climate change; topics neglected and often poorly understood by scholars and policymakers.